Analysis and Design of Three-Phase LLC Resonant Converter with Matrix Transformers - Jing-Yuan Lin; Hsuan-Yu Yueh; Yi-Feng Lin; Pin-Hsien Liu (Energies, 2022)
This study presents the topology of a three-phase LLC resonant converter with matrix transformers. The three-phase LLC resonant converter has the advantages of conventional LLC resonant converters, including zero-voltage switching at the primary side, zero-current switching at the secondary side, high-frequency feasibility, and high efficiency. Moreover, it has additional advantages that differ from conventional LLC, including low output capacitor current ripple, natural current sharing in three resonant currents, and a high power level. As a result of the above mentioned characteristics, LLC topology has been used in many electric vehicle charging systems, server power systems, and other high-power applications. However, as the power level becomes higher and higher, the input voltage is usually too high to reduce conduction loss, and the output current also increases. This situation makes transformer design more difficult. The increasing current means more core and copper loss, and the heat dissipation of the transformer becomes more difficult. Matrix transformer technology can improve this problem directly and simply. By utilizing matrix transformers, which are primary series connected and secondary parallel connected, the primary voltage stress and secondary current stress of the transformers can be reduced, and the output current can be distributed. The analysis of the proposed converter in this study includes a circuit operation introduction, a time-domain analysis, calculation of the transfer ratio curve in the frequency domain, and a loss analysis. The theoretical analysis and performance of the proposed converter are verified. A three-phase LLC resonant converter with matrix transformers prototype is built with a high input voltage of 800-VDC and high output current of 200-A. The output voltage is 100-VDC. The waveform and efficiency data will be shown in the experimental results.